2010
DOI: 10.1017/s0007485310000416
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive incompatibility between the B and Q biotypes of the whitefly Bemisia tabaci in China: genetic and behavioural evidence

Abstract: The B and Q 'biotypes' of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) have been invading many parts of the world and causing severe damage to a range of crops. Recent phylogenetic analyses indicate that B and Q are cryptic species within the B. tabaci species complex. Although various attempts have been made to examine the reproductive compatibility between B and Q, few studies have tested the fertility of the F1 females and so the extent of possible gene flow remains unclear. In this study, we conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
76
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 37 publications
7
76
0
2
Order By: Relevance
“…No hybrids were detected in our study, suggesting that they are genetically isolated in the field. This is consistent with (1) F ST values for MEAMI and Med B. tabaci estimated at national and sampling scales in Tunisia (0.31 B F ST B 0.58) and with the results of previous studies (Moya et al 2001;Simón et al 2007;Dalmon et al 2008), (2) the percentage divergence between Med and MEAMI mtCOI haplotypes in the present study (4.9-5.4%) and in different parts of the world (Boykin et al 2007;Dinsdale et al 2010) which identifies them as two distinct species, and (3) the widely reported reproductive incompatibility between the two species (Elbaz et al 2010;Xu et al 2010;De Barro et al 2011;Sun et al 2011). Currently, although Med and MEAMI species are the most frequently observed species in the Mediterranean basin, they are often observed separately (Bosco et al 2006;De la Rúa et al 2006;Tahiri et al 2006;Tsagkarakou et al 2007;Dalmon et al 2008;Vassiliou et al 2008).…”
Section: Co-occurrence Of Two B Tabaci Species In Tunisiasupporting
confidence: 85%
See 1 more Smart Citation
“…No hybrids were detected in our study, suggesting that they are genetically isolated in the field. This is consistent with (1) F ST values for MEAMI and Med B. tabaci estimated at national and sampling scales in Tunisia (0.31 B F ST B 0.58) and with the results of previous studies (Moya et al 2001;Simón et al 2007;Dalmon et al 2008), (2) the percentage divergence between Med and MEAMI mtCOI haplotypes in the present study (4.9-5.4%) and in different parts of the world (Boykin et al 2007;Dinsdale et al 2010) which identifies them as two distinct species, and (3) the widely reported reproductive incompatibility between the two species (Elbaz et al 2010;Xu et al 2010;De Barro et al 2011;Sun et al 2011). Currently, although Med and MEAMI species are the most frequently observed species in the Mediterranean basin, they are often observed separately (Bosco et al 2006;De la Rúa et al 2006;Tahiri et al 2006;Tsagkarakou et al 2007;Dalmon et al 2008;Vassiliou et al 2008).…”
Section: Co-occurrence Of Two B Tabaci Species In Tunisiasupporting
confidence: 85%
“…The whitefly B. tabaci is a complex containing at least 24 morphocryptic species (i.e., genetically distinct but morphologically indistinguishable), most of which are reproductively incompatible (Dinsdale et al 2010;Elbaz et al 2010;Xu et al 2010;Wang et al 2010;De Barro et al 2011;Sun et al 2011). Among the 24 B. tabaci putative species delineated by Dinsdale et al (2010), the Mediterranean (Med) and the Middle East-Asia Minor I (MEAMI) species, have attracted particular attention in the past 30 years.…”
mentioning
confidence: 99%
“…The two most distinct populations were BJabo, which might be because of geographic distance, and CPsoj, which might be because of the greater adaptation of the pest to the host plant and/or to the reproductive isolation. Previous studies have confirmed that specific populations reproductively isolated because of copulation and post-copulation barriers (Wang et al, 2010;Xu et al, 2010;Sun et al, 2011).…”
Section: Genetic Structurementioning
confidence: 77%
“…The sequencing effort also demonstrated that several apparently shared alleles at the Bem6 locus were homoplasious, having evolved independently via different insertions and deletions at multiple heptanucleotide tandem repeats, but producing DNA fragments of identical size. Biotypes B and Q belong to genetically distinct but morphologically indistinguishable species in the Bemisia tabaci species complex (De Barro et al 2011) and are reproductively incompatible (Elbaz et al 2010, Sun et al 2011. Hybrids are rarely produced in the laboratory and are sterile (Sun et al 2011).…”
Section: Resultsmentioning
confidence: 99%